Kontribusi Koperasi Syariah Dalam Meningkatkan Kesejahteraan Guru, Studi Analisis Pembiayaan Bmt Rizqona Ikabu Jombang - Amin Awal Amarudin; Septi Dwi Andini (Ekosiana Jurnal Ekonomi Syari ah, 2023)
In this study, the authors aimed to analyze how the strategy for implementing BMT Rizqona IKABU financing for teachers in Islamic boarding schools and how the impact of the strategy for implementing BMT Rizqona IKABU financing was for teachers in Islamic boarding schools so that they would know how the contribution of financing for teachers at BMT Rizqona had on teacher welfare. In this study, the authors used qualitative methods. In collecting data the authors searched from documents and participants, namely through interviews and observations with administrators and teacher customers of BMT Rizqona IKABU. In analyzing the data, the writer uses the Miles and Huberman model analysis, namely by reducing data, presenting data, and drawing conclusions or verification. The results of the study conclude that there are several financing contributions for teachers who are given BMT Rizqona IKABU to teacher welfare, namely spiritual welfare financing contributes to helping teachers carry out worship (in the form of zakat, infaq and alms), on social welfare financing contributes to helping teachers meet educational needs personal and family members, to the welfare of the soul financing contributes to assisting teachers in maintaining or meeting the health needs of teachers, to economic welfare financing contributes to assisting teachers in meeting the needs of purchasing goods and teacher business needs. Kata Kunci: Sharia cooperatives, financing, welfare, teachers